42.3k views
5 votes
Y= 2x
-6x+3y=16
Solve using substitution

User Ronel
by
5.6k points

1 Answer

1 vote

Answer:

No Solution

Explanation:

Substitution means to replace the variable with the one provided, in this problem we have been given y = 2x, so we would simply replace the y variable in the second equation with 2x.

Review over what we have been given

y = 2x

-6x + 3y = 16

As explained above, substitute the y value in the second equation with the contents of the first equation.

-6x + 3(2x) = 16

In this step, you can solve for the value of x.

-6x + 6x = 16

Since both of the x variables cancel out, we cannot find the value of x since it equals to zero, which also means we cannot find the value of y.

0 = 16

Generally, we find the value of our x, then we would input that into the first equation to find the value of y.

But as stated above, there is no value of x, therefore there is no solution.

User Larrywgray
by
5.6k points